Evaluation of Wearable Sensor Devices in Parkinson's Disease: A Review of Current Status and Future Prospects. (23rd September 2020) - Lu, Ruirui; Xu, Yan; Li, Xiaohui; Fan, Yongli; Zeng, Weiqi; Tan, Yang; Ren, Kang; Chen, Wenwu; Cao, Xuebing
Abstract : Parkinson's disease (PD) decreases the quality of life of the affected individuals. The incidence of PD is expected to increase given the growing aging population. Motor symptoms associated with PD render the patients unable to self-care and function properly. Given that several drugs have been developed to control motor symptoms, highly sensitive scales for clinical evaluation of drug efficacy are needed. Among such scales, the objective and continuous evaluation of wearable devices is increasingly utilized by clinicians and patients. Several electronic technologies have revolutionized the clinical monitoring of PD development, especially its motor symptoms. Here, we review and discuss the recent advances in the development of wearable devices for bradykinesia, tremor, gait, and myotonia. Our aim is to capture the experiences of patients and clinicians, as well as expand our understanding on the application of wearable technology. In so-doing, we lay the foundation for further research into the use of wearable technology in the management of PD.